Psychosocial health in families with children with Autistic Spectrum Disorders - Ευστρατοπούλου, Μαρία; Μιλτσακάκη, Στεφανία; Πλιόγκου, Βασιλική (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The present study aimed to investigate depressive symptoms in families having a child with Autistic Spectrum Disorders. For the estimation of depression symptoms in parents, (N=58) the Βeck Depression Inventory (B.D.I; Beck &Beamesderfer, 1974) was used and for the assessment of depressive symptoms in siblings (N=28) the Youth Self Report (YSR; Achenbach &Rescorla, 2001) was used. Analysis of the data revealed the presence of depressive symptoms in parents with mothers having higher scores in BDI than their husbands. In addition, the presence of depressive symptoms in one of the parents was significant correlated with depressive symptoms in their partners. The analysis of the results concerning the presence of depressive symptoms in siblings revealed that there were no symptoms of depression and their internalizing scores were at typical range. For the interpretation of the results many individual, family and social factors were under consideration.